Emotional intelligence as a key factor for international success in education - Павлова, А. І. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The article discusses the critical role of emotional intelligence in the field of international education. The influence of emotional intelligence on cross cultural dialogue is considered. The role of educators in fostering emotional intelligence through innovative teaching methodologies is emphasized.

У статті обговорюється критична роль емоційного інтелекту в галузі міжнародної освіти. Розглядається вплив емоційного інтелекту на міжкультурний діалог. Особлива увага приділяється ролі педагогів у розвитку емоційного інтелекту за допомогою інноваційних методів викладання.
Keywords: emotional intelligence; cross-cultural understanding; innovative teaching methods; емоційний інтелект; міжкультурне розуміння; інноваційні методи викладання